Pengaruh Kualitas Pelayanan dan Kelengkapan Produk Terhadap Kepuasan Kosumen di Toko Buku Zanafa 2 Cabang Marpoyan - Nur Ikhsan, Wandi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study was to determine the effect of service quality and product completeness on consumer satisfaction at Zanafa Bookstore 2 Marpoyan Branch. The sample in this study were consumers at Zanafa Bookstore 2 Marpoyan Branch totaling 96 respondents. The variables studied in this study were the Service Quality variable, the Product Completeness variable and the Consumer Satisfaction variable. The data analysis used multiple linear regression methods using validity tests, reliability tests, normality tests, heteroscedasticity tests, multiple linear regression tests, partial t tests, f tests, determination coefficient tests (R2) with the help of SPSS. The test was carried out in order to determine the effect of independent variables and dependent variables. Based on the results of the study, it shows that partially and simultaneously there is an influence between the price and service quality variables on consumer satisfaction of 27.4% and the remaining 72.6% is influenced by other factors outside the study. After conducting a partial t-test on the Service Quality variable X1 where t count = 3.833 t table 1.985 and a significant probability value of 0.005 0.05, and the Product Completeness variable X2 where t count = 4.658 t table 1.985 and a significant probability value of 0.077 0.05. After conducting the f test, the F count number (17.569) F table (3.094) was obtained, while the multiple linear regression equation is as follows. Y = 75.162 + 0.361 x1 + 0.363 x2 + e